Mechanistic investigation on copper-arylacetylide polymerization and sensing applications - Liang, Quanduo; Chang, Xiaoyong; Su, Ya-qiong; Mugo, Samuel; Zhang, Qiang (My University, 2021)
Exploration of new polymerization reactions is very intriguing in fundamental and practical research, which will advance reaction theories and produce various functional materials. Herein, we report a new polymerization method based on the reaction of CuI and arylacetylide, which generates linear polymers with high molecular weight and low polydispersity index of molecular weight. The Cu–arylacetylide polymerization exhibits different characteristics with traditional polymerizations such as mild reaction temperature, air atmosphere reaction, high molecular weight, fast polymerization rate, and imprecise molar ratio between monomers. The bond formation path and activation energy of each step was investigated by density functional theory calculations to understand the reaction mechanism. The poly(Cu-arylacetylide)s exhibit strong fluorescence emission and inherent semiconductive properties, which have been used to fabricate an electronic device for streptavidin sensing.
Keywords: polymerization methods